Orbital decompression improves visual function and macular blood perfusion status in patients with thyroid-related eye disease - Wu, Bingxuan; Zhu, Min; Zhang, Feng; Cao, Jiamin; Xie, Bingyu; Zhu, Ziyi; Xiong, Wei (Frontiers in Medicine, 2024)
Background Orbital decompression surgery is a treatment option for Thyroid-associated Ophthalmopathy (TAO). However, its effects on visual function and macular perfusion status remain unclear. This study examined how orbital decompression surgery affects visual acuity and macular blood flow in TAO patients and the variation between these two factors. Methods This study involved cross-sectional and longitudinal analyses of 54 TAO patients, who were categorized into a normal vision group (n = 40) and an impaired vision group (n = 14) based on the presence of visual impairment before surgery (LogMAR BCVA >0.097). Among the participants, 20 underwent orbital decompression surgery (normal vision group: n = 13, impaired vision group: n = 7). BCVA and IOP were assessed at baseline in patients with TAO, and macular retinal blood perfusion indices were measured using OCTA. One month post-operatively, changes in these indices were compared between the two groups, and the correlation between visual acuity and macular perfusion indices was analyzed. Results The LogMar BCVA in the visual impairment group was significantly worse than that in the normal vision group (p < 0.001), while the W-MVD was significantly lower (p = 0.01). In the visual impairment group, post-operative LogMar BCVA improved significantly (p = 0.038), and W-MVD increased significantly (p = 0.008) compared to baseline. However, there were no significant changes in LogMar BCVA, S-MVD, D-MVD, or W-MVD in the normal vision group from preoperative to postoperative assessments. A strong negative correlation was found between the changes in W-MVD and changes in LogMar BCVA in the eyes of the visual impairment group treated with orbital decompression (Pearson correlation coefficient, R = −0.812, p = 0.05). Conclusion This study found that TAO patients with visual impairment had lower macular blood flow perfusion than those with normal vision. Endoscopic orbital decompression surgery was found to improve both the best-corrected visual acuity and macular blood flow perfusion in TAO patients with visual impairment, and the improvement in visual acuity was correlated with the improvement in macular blood flow perfusion.